PODCAST ENGLISH FOR SPECIFIC PURPOSES’ STUDENTS OF THE NURSING DEPARTMENT, IS IT HELPFUL TO HELP THEM ? - Mandasari, Yuyun Putri; Wulandari, Eka; Savage, Eileen (SYNTIFIC, 2024)
Background. The students of health departments face many challenges in learning English for their career in the future, including four language skills and components. In the era of technological advances, there are alternatives to help students improve their English competencies, one of them using Podcast media. Some studies revealed that Podcasts are interactive media in teaching and learning and are useful to give students more meaningful learning experiences for real life. This study aimed to determine the ESP students’ point of view on using Podcasts to learn English. Research Method. The writer employed mixed method research with quantitative and qualitative research with approach survey research and interviews to collect data. Ninety-six (96) nursing department students were the participants/respondents of this study; online questionnaires to find out students’ points of view and interviews were used to collect the data. The data found were analyzed quantitively and descriptively. Findings. The result showed that more than 75% of respondents had positive perceptions of Podcast use in English language learning. The students also had positive comments during the interview about the Podcasts used in the classroom. Conclusion. Podcasts have some benefits to be used in English language learning as one of the alternatives of education media both online and offline mode.